Are scientific ideas compatible with personal interests? An application of game theory - García Bermejo-Ochoa, Juan Carlos (Estudios Económicos de El Colegio de México, 2001)
Is the reward system efficient to achieve that scientists take the research decisions that contribute most to the epistemic growth of their discipline? This paper approaches this question with regard to a wide class of games. By means of some very simple examples, it shows how easily it may happen that incentives get distorted, even if all members of the scientific community share a common epistemic point of view, every obtained result is published, there are not redundant results, contributions are evaluated by direct inspection, and scientists are rewarded according to their relative performance.